Diffuse Neuroendocrine Cell Hyperplasia: Report of Two Cases - Cevriye Cansız Ersöz; Ayten Kayı Cangır; Serpil Dizbay Sak (Case Reports in Pathology)
Diffuse idiopathic pulmonary neuroendocrine cell hyperplasia (DIPNECH) is a rare pulmonary disorder characterised by a proliferation of neuroendocrine cells within the lung. It is believed that a minority of the patients with DIPNECH can develop carcinoid tumors. Here, we report two new cases of DIPNECH with coexisting carcinoid tumors.